THE CORRELATION OF CONFORMITY AND SELF CONTROL WITH SMOKING BEHAVIOR AT GIRL ADOLESCENT IN SURAKARTA - Hapsari Harahap, Elfira Wahyu (Universitas Sahid Surakarta, 2015)
ThisÂ researchÂ purposeÂ toÂ knowingÂ theÂ correlationÂ betweenÂ conformity withsmoking behavior at girl adolescent in Surakarta, to knowing the correlationbetween selfÂ controlÂ withÂ smokingÂ behaviorÂ atÂ girlÂ adolescentÂ inÂ SurakartaÂ andÂ toknowingÂ the correlation between conformity and self control with smoking behaviorat girl adolescent in Surakarta.This research used quantitative correlation approach with using scale ascollector ofÂ researchÂ dataÂ whichÂ isÂ inÂ conformityÂ scaleÂ form,Â selfÂ controlÂ scaleÂ andsmoking behavior scale. Population in this research is girl adolescent in Surakartawith sample as much as 55 persons are taken by incidental sampling. The dataanalyze technique in this research use the double linear regression analysis assisteduse SPPS Statistical Package for Social Sciences) for Windows Release 21,0program.The double linier regression analysis result that there is significancecorrelation between conformity with smoking behavior at girl adolescent inSurakarta get obtained Ï value equal to 0,039 < 0,05. So also there is significancecorrelation between self control with smoking behavior at girl adolescent inSurakarta, proofed to be obtain Ï value equal to 0,000 < 0,05. By together is alsoknown that there is significance correlation between conformity and self control withsmoking behavior at girl adolescent in Surakarta, proof Ï value equal to 0,000 <0,05. Excelsior conformity so higher the girl adolescent smoking behaviorÂ andprogressivelyÂ goodnessÂ selfÂ controlÂ ofÂ henceÂ progressivelyÂ lowerÂ theÂ girl adolescentsmoking behavior in Surakarta.Key word: smoking behavior, conformity, self control